Studi kualitatif faktor yang mempengaruhi orang tua dalam pemberian makan anak autis - Camelia, Rusda; Wijayanti, Hartanti Sandi; Nissa, Choirun (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Children with Autism Spectrum Disorder (ASD) have problem in metabolism which makes them have limited food intake. The implementation of the diet is influenced by eating behaviors in children with ASD and parents in feeding children.Objective: This study was to analyze eating behaviors and factors influencing parents on child’s feeding.Methods: This quallitative study was using in-dept interviews to parents as informants. Observations related to children's eating habits and behaviors also conducted in this study. FFQ was also conducted to measure gluten and casein consumptions. The retrieval of subjects through purposive sampling based on inclusion criteria, there was 8 children with ASD aged 6-14 years old with their care taker as informans who were willing to join this study. Results: Children with ASD have unique food preferention and able to expres hunger and satiety amid the limitatins of social interaction. Gluten intake is more often consumed (26,63 times/week) than casein (5,25 times/week). 25% parents are implementating the diet and based on knowledges, obey the doctor or terapies, improve children’s behavioral experiences after diet, motivation, skills in processing food diets, purchasing power, and family supports. Parents are not implementating the diet because of children’s responses, informant’s worries, sibling behaviors who offer non-dietary food, limited dietary food in arround, and limited time to process dietary food.Conclusion: Eating behaviors’s subject is related to parent’s feeding. Feeding by informants are influenced by children’s responses, knowledges, attitudes, experiences and motivations, skills, purchasing power, availability of food, sibling behaviors, time, and family supports. Knowledges, motivations, and family support were the most important factors in feeding children with autism.